2020
DOI: 10.1093/cid/ciaa1512
|View full text |Cite
|
Sign up to set email alerts
|

Reducing Catheter-associated Urinary Tract Infections via Cost-saving Diagnostic Stewardship

Abstract: We conducted a quality improvement project at our large, public, tertiary-care, academic hospital to reduce the Standardized Infection Ratio (SIR) of hospital-acquired Catheter Associated Urinary Tract Infections (CAUTIs). Our diagnostic stewardship program, based on education and audit and feedback, significantly reduced inpatient urine culture orders and CAUTI SIR.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 7 publications
0
11
0
1
Order By: Relevance
“…In addition, a hospital-wide screensaver encouraged providers to stop sending urine cultures as part of routine nosocomial fever workups. These combined interventions reduced monthly urine cultures to half across most intensive care units and wards, with a corresponding decrease in CAUTI [57].…”
Section: Cognitive Aids Rules and Policiesmentioning
confidence: 99%
“…In addition, a hospital-wide screensaver encouraged providers to stop sending urine cultures as part of routine nosocomial fever workups. These combined interventions reduced monthly urine cultures to half across most intensive care units and wards, with a corresponding decrease in CAUTI [57].…”
Section: Cognitive Aids Rules and Policiesmentioning
confidence: 99%
“…Diagnostic stewardship strategies could be effective in the treatment and prevention of NHSN CAUTI. 27,29,30 When interventions are implemented to prevent CAUTI, improved outcomes expected are reduced CAUTI, reduced indwelling urethral catheter use, reduced collection and antibiotic use for positive urine cultures, reduced antibiotic-associated complications, and reduced costs associated with these outcomes.…”
Section: Additional Approachesmentioning
confidence: 99%
“…The educational sessions may outline the evidence behind guidelines and the goals of the program and may target specific aspects of CAUTI prevention. Provide education on the following topics: Appropriate catheter care 139141,145,149153 Appropriate indications for catheter insertion 138,139,143,147,151,154,155 Insertion technique 141,144,149,151154 Urine-culture indications, guidance on collection, storage, and transport of urine cultures Hand hygiene education 149 , 151 , 152 Alternatives for indwelling catheters, including to patient and family 66,145,156,157 Management of urinary retention Patient transportation. 66 Provide educational materials as follows: Daily assessment of need for catheter 147,158,159 Decision-making algorithm for catheter indication and urine-culture ordering 139 Case-based education by the infection prevention or stewardship team 139,160 Unit-based educational materials 161 Online learning materials 61,145 Novel cognitive aids—screensaver, hospital leadership memorandum 29 Patient and family educational materials 145 Checklists for resident physicians 162 Simulation training on catheter insertion and maintenance. 61 …”
Section: Section 6: Implementation Strategiesmentioning
confidence: 99%
“…While implementation of CPOE and CDS tools appear to result in a modest reduction in unnecessary urine culture requests, studies have shown that DS pre-analytic strategies were most effective when coupled with antibiotic stewardship-led educational support and clinician/infectious disease physician direction in devising appropriate EMR order prompts [20]. Effective interventions include a lecture series with case-based vignettes, institutional developed pocket cards with easy-to-reference diagnostic algorithms for UTI, and evidence-based guidelines with preferred treatment regimen and duration of therapy [22,25,35,[43][44][45][46][47]. One example of the effectiveness of educational objectives involved a multi-interventional approach.…”
Section: Pre-analytical Urinary Stewardship Interventionsmentioning
confidence: 99%
“…A lecture to the department of surgery and department of medicine on appropriate urine culture diagnostics was held, followed by individualized educational monthly sessions with nursing leadership from each care unit, informationtechnology (IT) computer screensaver reminders, and random chart review by infection control staff with monthly provider-specific feedback. This was combined with hospital administration support and ultimately resulted in a near 50% reduction in urine culture orders (post-interventional 280 compared to 509 urine cultures monthly) without any observed change in patient mortality [44]. Similarly, Trautner et al implemented a streamlined diagnostic algorithm for ASB and CAUTI combined with case-based audit and feedback at a Veterans Affairs (VA) health system.…”
Section: Pre-analytical Urinary Stewardship Interventionsmentioning
confidence: 99%